Developmental venous anomaly in adult patients with diffuse glioma: A clinically relevant coexistence?. (1st January 2019) - Roux, Alexandre; Edjlali, Myriam; Porelli, Sayuri; Tauziede-Espariat, Arnault; Zanello, Marc; Dezamis, Edouard; Zah-Bi, Gilles; Sanson, Marc; Puget, Stéphanie; Capelle, Laurent; Varlet, Pascale; Oppenheim, Catherine; et al.
Abstract : Objective: To determine the prevalence of developmental venous anomaly in adult patients with diffuse glioma. Methods: We performed a retrospective cohort study (2010–2016) of consecutive adult patients harboring a supratentorial diffuse glioma in 2 centers: Sainte-Anne Hospital (experimental and control sets) and Pitié-Salpêtrière Hospital (external validation set). We included 219 patients with diffuse glioma (experimental set), 252 patients with brain metastasis (control set), and 200 patients with diffuse glioma (validation set). The inclusion criteria were age ≥18 years at diagnosis, histopathologic diagnosis of diffuse glioma according to the 2016 World Health Organization classification of tumors of the CNS, surgery as first-line treatment without previous oncologic treatment, available presurgical MRI performed with similar acquisition protocol, and absence of a nodular-like or a ring-like pattern of contrast enhancement on MRI that may preclude the identification of a possible developmental venous anomaly within the glioma. Results: We found more developmental venous anomaly in the experimental set (21.5%) than in the control set (5.2%, p < 0.001). Similarly, we found more developmental venous anomaly in the validation set (23.5%) than in the control set (5.2%, p < 0.001). There was no difference in the developmental venous anomaly prevalence between the experimental and validation sets. The developmental venous anomaly distribution was not significantly associated with histopathologic, molecular, or imaging findings of the diffuse gliomas. Conclusions: We report and replicate in an external cohort a high prevalence of developmental venous anomaly in adult patients with diffuse glioma, which suggests a potential underlying common predisposition or a causal relationship that requires deeper investigations.